Pedagogical and educational guidance in the Ginásios Vocacionais: interfaces between pedagogy and psychology (1961-1970) - Chiozzini, Daniel Ferraz (2022)
The article consists in part of an investigation about the interfaces between Pedagogy and Psychology in Ginásios Vocacionais, public secondary schools existing between 1961 and 1970 in the state of São Paulo. Primary sources that recorded work on Pedagogical Guidance (OP) and Educational Guidance (OE) were analyzed and compared with the reference bibliography, making it possible to identify these areas of the curriculum as a privileged space in the relationship between Pedagogy and Psychology, mainly due to the themes addressed and evidence from authors who supported the pedagogical practice. In this sense, two themes that gained prominence in school work were selected and analyzed: composition of teams of group work and sexual education. It was also noted, however, a difficulty in determining the specificity of each of the two areas and some emblematic changes in the text of the primary sources used, possibly due to the external and internal political changes to schools that occurred since 1967.